Evaluation Of The Relocation Policy For Traders In Mardika Market Ambon: Impact On Social And Economic Life - Maryam Salampessy; Said Lestaluhu; Josep Antonius Ufi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study aims to evaluate the relocation policy of traders in Mardika Market, Ambon, as well as its impact on the social and economic life of the local community. The relocation policies implemented by local governments aim to improve market infrastructure and create a more orderly trading environment. However, the impact of these policies on traders and consumers is not yet fully understood. The methodology used in this study includes a qualitative approach with data collection through in-depth interviews, field observations, and document analysis. Respondents consisted of traders involved in relocation, consumers, and the government. The results show that relocation has had a positive impact in terms of increased accessibility and convenience for consumers, but it has also posed challenges for merchants, such as increased operational costs and loss of repeat customers. This study highlights the importance of considering social and economic aspects in relocation policy planning. Recommendations for the government include the need for ongoing support for affected traders, as well as strategies to increase public involvement in the decision-making process related to market policies